Ectopic parathyroid adenoma in the pyriform sinus. Issue 10 (25th July 2017) - Kim, Jonathan; Cubangbang, Maricel; Adkins, Lacey; Chia, Stanley; DeKlotz, Timothy R.; Boyle, Lisa; Davidson, Bruce
Abstract: Background: Ectopic parathyroid glands may complicate the surgical approach to primary hyperparathyroidism. We describe a rare ectopic parathyroid location, the pyriform sinus. Methods: Three patients, 2 after prior unsuccessful parathyroid exploration, were found to have ectopic parathyroid adenomas in the pyriform sinus. Two cases were identified by 4D‐CT of the neck. The other was localized by a technetium 99m sestamibi single photon emission CT (SPECT). In each case, office endoscopy confirmed the lesions. The patients were treated by either transoral laser or robotic resection of the parathyroid adenoma. Results: After surgery, the patients had resolution of their hyperparathyroidism. Conclusion: Ectopic parathyroid adenomas in the pyriform sinus are rare, but should be considered in those patients who have had a failed neck exploration and in those who undergo 4D‐CT scanning or SPECT scanning.